2022
DOI: 10.3390/vaccines10020136
|View full text |Cite
|
Sign up to set email alerts
|

Age and Primary Vaccination Background Influence the Plasma Cell Response to Pertussis Booster Vaccination

Abstract: Pertussis is a vaccine-preventable disease caused by the bacterium Bordetella pertussis. Over the past years, the incidence and mortality of pertussis increased significantly. A possible cause is the switch from whole-cell to acellular pertussis vaccines, although other factors may also contribute. Here, we applied high-dimensional flow cytometry to investigate changes in B cells in individuals of different ages and distinct priming backgrounds upon administration of an acellular pertussis booster vaccine. Par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Whether this re-oriented profile of B cell response is long-lasting or wanes soon after revaccination has not been confirmed. Additionally, high-dimensional flow cytometry was used to characterize the kinetics of B cell subsets circulating in the blood of human subjects of different ages and different priming backgrounds upon administration of an aP booster [ 72 ]. Diks et al showed that the total and IgG1+ plasma cell responses were stronger in subjects primed with wP vaccines than in individuals primed with aP vaccine [ 72 ].…”
Section: Acellular and Whole-cell Pertussis Vaccine Induce Different ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Whether this re-oriented profile of B cell response is long-lasting or wanes soon after revaccination has not been confirmed. Additionally, high-dimensional flow cytometry was used to characterize the kinetics of B cell subsets circulating in the blood of human subjects of different ages and different priming backgrounds upon administration of an aP booster [ 72 ]. Diks et al showed that the total and IgG1+ plasma cell responses were stronger in subjects primed with wP vaccines than in individuals primed with aP vaccine [ 72 ].…”
Section: Acellular and Whole-cell Pertussis Vaccine Induce Different ...mentioning
confidence: 99%
“…Additionally, high-dimensional flow cytometry was used to characterize the kinetics of B cell subsets circulating in the blood of human subjects of different ages and different priming backgrounds upon administration of an aP booster [ 72 ]. Diks et al showed that the total and IgG1+ plasma cell responses were stronger in subjects primed with wP vaccines than in individuals primed with aP vaccine [ 72 ]. Consistently with these data, results showing significantly higher IgG4 levels in children who had received an aP vaccine at primary immunization than those in children who had received a wP vaccine were presented at the World Association for Infectious Diseases and Immune Disorders (WAidid) Congress [ 68 ].…”
Section: Acellular and Whole-cell Pertussis Vaccine Induce Different ...mentioning
confidence: 99%
“…A limitation of this study was the high heterogeneity observed between donors, which is also described by others ( 50 ), together with the low sample size and limited sampling time points, therefore just limited differences between the cohorts were assessed. Moreover, the differences found might be affected by external factors, although all donors were vaccinated, and blood was collected in the same season and time of the day.…”
Section: Discussionmentioning
confidence: 94%
“…For our analysis, the small number of participants for this comparison limited the power to detect a significant difference. However, significant differences between aP and wP primed individuals have been reported in a subset of the study participants using high dimensional flow-cytometric analyses showing significantly stronger IgG1+ plasma cell responses in wP primed individuals, which was the most prominent subclass at day 7 ( 36 ). Also stronger Th2 responses were reported in aP primed versus wP primed individuals ( 37 ).…”
Section: Discussionmentioning
confidence: 97%